Cognitive stimulation therapy as a sustainable intervention for dementia in sub-Saharan Africa: feasibility and clinical efficacy using a stepped-wedge design. (22nd February 2017) - Paddick, Stella-Maria; Mkenda, Sarah; Mbowe, Godfrey; Kisoli, Aloyce; Gray, William K.; Dotchin, Catherine L.; Ternent, Laura; Ogunniyi, Adesola; Kissima, John; Olakehinde, Olaide; Mushi, Declare; Walker, Richard W.
ABSTRACT: Background: Cognitive stimulation therapy (CST) is a psychosocial group-based intervention for dementia shown to improve cognition and quality of life with a similar efficacy to cholinesterase inhibitors. Since CST can be delivered by non-specialist healthcare workers, it has potential for use in low-resource environments, such as sub-Saharan Africa (SSA). We aimed to assess the feasibility and clinical effectiveness of CST in rural Tanzania using a stepped-wedge design. Methods: Participants and their carers were recruited through a community dementia screening program. Inclusion criteria were DSM-IV diagnosis of dementia of mild/moderate severity following detailed assessment. No participant had a previous diagnosis of dementia and none were taking a cholinesterase inhibitor. Primary outcomes related to the feasibility of conducting CST in this setting. Key clinical outcomes were changes in quality of life and cognition. The assessing team was blind to treatment group membership. Results: Thirty four participants with mild/moderate dementia were allocated to four CST groups. Attendance rates were high (85%) and we were able to complete all 14 sessions for each group within the seven week timeframe. Substantial improvements in cognition, anxiety, and behavioral symptoms were noted following CST, with smaller improvements in quality of life measures. The number needed to treat was two for a four-point cognitive (adapted Alzheimer's Disease Assessment Scale-Cognitive) improvement. Conclusions: This intervention has the potential to be low-cost, sustainable, and adaptable to other settings across SSA, particularly if it can be delivered by non-specialist health workers.